Prefrontal Cortex Neuromodulation Improves Motor-Cognitive Components in Latinx Hispanic People Living with HIV (International Journal of Physiotherapy, 2022)
Background: HIV is an immunodeficiency virus that currently has no cure but is managed with antiretroviral medication (ART). ART has increased the life expectancy of those living with HIV. Evidence shows a correlation between the increase in life expectancy and increases in neurological motor-cognitive impairments, thus leading to a decline in functional mobility and overall quality of life. The current study aimed to address neurological motor cognitive impairments in Latinx HIV+ individuals using transcranial direct current stimulation (tDCS).Methods: Female and male participants, ages 18-65, with an HIV diagnosis by a medical doctor and a CD4 count of >300 were obtained from an HIV clinic in La Perla de Gran Precio in Puerto Rico. Spatiotemporal data were collected; each subject participated in a dual cognitive ambulation task and completed the HIV dementia scale.Results: Dual cognitive tasks were calculated for cadence, gait cycle, gait speed, single limb, double limb, stance, stride, swing, and sway were analyzed. After the application of tDCS, the only statistically significant difference found among the subjects was an improvement in gait speed (p≤.05). In addition, the cognitive component showed an improvement in the HIV dementia scale total (p≤.05), including an increase in motor speed and memory recall (p≤.05).Conclusion: tDCS may be a feasible and effective treatment option for this population to alleviate motor-cognitive alterations in those living with HIV. Future research should consider the benefits of tDCS combined with diverse training, such as gait or balance activities.